Meningkatkan keterlibatan aktif siswa kelas VIII F SMPN 1 Pontianak melalui penerapan talking chips - St. Dwi Karmila (Indonesian Journal of Educational Development, 2021)
This classroom action research aims to increase the active engagement of VIII F students of SMPN 1 Pontianak through the application of Talking Chips. The subjects of this study were 30 VIII F students of SMPN 1 Pontianak semester 2 in the academic year 2020/2021. The object of research is the active engagement of students in learning English. Data collection methods used were observation and opinion questionnaires. The data were then analyzed using descriptive methods. The criterion for the success of the research was the active engagement of students in the category of active or very active. This research was conducted in two cycles. The results showed that the active engagement of students was in the very active category visually and in the active category verbally, listening, writing and emotionally. Furthermore, the results of the students' questionnaire showed the talking chips strategy succeeded in increasing their active engagement in learning English. The conclusion of this research is that the application of the Talking Chips strategy can increase the active engagement of students. Penelitian tindakan kelas ini bertujuan untuk meningkatkan keterlibatan aktif siswa kelas VIII F SMPN 1 Pontianak melalui penerapan Talking Chips. Subjek penelitian ini adalah siswa kelas VIII F SMPN 1 Pontianak semester genap tahun pelajaran 2020/2021 yang berjumlah 30 orang. Sedangkan objek penelitian adalah keterlibatan aktif siswa dalam pembelajaran Bahasa Inggris. Metode pengumpulan data yang digunakan adalah observasi dan angket pendapat (Questionnaire). Data kemudian dianalisis dengan metode deskriptif. Kriteria keberhasilan penelitian adalah keterlibatan aktif siswa dikategorikan aktif atau sangat aktif. Penelitian ini dilakukan dalam dua siklus. Hasil penelitian menunjukkan keterlibatan aktif siswa ada pada kategori sangat aktif secara visual dan ada pada kategori aktif secara lisan, mendengarkan, menulis dan secara emosional. Selanjutnya, hasil dari questionnaire siswa menunjukkan strategi talking chips berhasil meningkatkan keterlibatan aktif mereka dalam pembelajaran Bahasa Inggris. Kesimpulan yang diperoleh dari penelitian ini adalah penerapan strategi Talking Chips dapat meningkatkan keterlibatan aktif siswa.